Deep nightside photoelectron observations by MAVEN SWEA: Implications for Martian northern hemispheric magnetic topology and nightside ionosphere source. Issue 17 (10th September 2016) - Xu, Shaosui; Mitchell, David; Liemohn, Michael; Dong, Chuanfei; Bougher, Stephen; Fillingim, Matthew; Lillis, Robert; McFadden, James; Mazelle, Christian; Connerney, Jack; Jakosky, Bruce
Abstract: The Mars Atmosphere and Volatile EvolutioN (MAVEN) mission samples the Mars ionosphere down to altitudes of ∼150 km over a wide range of local times and solar zenith angles. On 5 January 2015 (Orbit 520) when the spacecraft was in darkness at high northern latitudes (solar zenith angle, SZA >120°; latitude >60°), the Solar Wind Electron Analyzer (SWEA) instrument observed photoelectrons at altitudes below 200 km. Such observations imply the presence of closed crustal magnetic field loops that cross the terminator and extend thousands of kilometers to the deep nightside. This occurs over the weak northern crustal magnetic source regions, where the magnetic field has been thought to be dominated by draped interplanetary magnetic fields (IMF). Such a day‐night magnetic connectivity also provides a source of plasma and energy to the deep nightside. Simulations with the SuperThermal Electron Transport (STET) model show that photoelectron fluxes measured by SWEA precipitating onto the nightside atmosphere provide a source of ionization that can account for the O 2 + density measured by the Suprathermal and Thermal Ion Composition (STATIC) instrument below 200 km. This finding indicates another channel for Martian energy redistribution to the deep nightside and consequently localized ionosphere patches and potentially aurora. Key Points: MAVEN SWEA instrument observed photoelectrons at altitudes below 200 km in deep nightside It suggests the presence of large cross‐terminator closed crustal magnetic field loops over the Martian northern hemisphere Such topologies also provide new energy sources to the nightside ionosphere